Boron‐free small modular pressurized water reactor design with new burnable absorber. (6th July 2016) - Choe, Jiwon; Zheng, Youqi; Lee, Deokjung; Shin, Ho Cheol
Summary: This paper presents a preliminary design of a Small Modular Pressurized Water Reactor (SMPWR) aimed at boron‐free operation which can reduce the size of a nuclear power plant (NPP) and the amount of liquid radioactive waste, and also reduce the corrosion issues caused by boric acid in the coolant. The design parameter limits, such as reactivity swing, axial offset (AO), 3D pin peaking factor (Fq), and the required shutdown margin, have been established for the boron‐free SMPWR. Furthermore, a new ring type of burnable absorber (R‐BA) with Zr– 167 Er is adopted as a burnable absorber (BA) and HfB2 is adopted as a control rod material to satisfy those design limits without liquid boron. Optimal fuel assemblies (FAs) and loading patterns have been searched through a sensitivity study, and the excess reactivity control capacity and design requirements have been demonstrated to be satisfactory. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This paper presents a preliminary design of a Small Modular Pressurized Water Reactor aimed at boron‐free operation. A new ring type of burnable absorber (R‐BA) with Zr– 167 Er is adopted as a BA, and HfB2 is adopted as a control rod material. Optimal fuel assemblies and loading patterns have been searched, and the reactivity control capacity and design requirements have been demonstrated.